2022
DOI: 10.1002/cbin.11961
|View full text |Cite
|
Sign up to set email alerts
|

DACH1 inhibits the proliferation and migration of papillary thyroid carcinoma

Abstract: DACH1 is an important component of the retinal determinate gene network (RDGN), which regulates the expression of target genes by directly binding or interacting with other factors. DACH1 shows inhibitory effects in most tumors, but its role in papillary thyroid carcinoma is unclear and warrants further investigation. We assessed the expression of DACH1 in different tissues and correlation with immune infiltration by The Cancer Genome Atlas (TCGA) and Tumor Immune Estimation Resource (TIMMER2.0 databases). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Several studies showed that DACH1 plays a significant role in the regulation of cell fate. 14 , 15 Could DACH1 be involved in the regulation of ferroptosis? To address this possibility, we first evaluated DACH1 mRNA and protein expression during HSC ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that DACH1 plays a significant role in the regulation of cell fate. 14 , 15 Could DACH1 be involved in the regulation of ferroptosis? To address this possibility, we first evaluated DACH1 mRNA and protein expression during HSC ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Dachshund homolog 1 (DACH1) is recognized as a crucial cell fate determination factor that regulates many important cellular life activities. 14 , 15 DACH1 was reported to induce cell apoptosis and arrest the cell cycle in the G2/M phase by upregulating p53 expression in HCC. 14 Moreover, DACH1 was showed to inhibit the proliferation and migration of papillary thyroid carcinoma via interacting with various cytokines such as C-X-C motif ligand8 and C-X-C motif ligand12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation